Pengaruh Insentif dan Punishment terhadap Kinerja Driver Grab Bike Kota Palembang - Wulandari, Shelfi; Veronica, Meilin; Emilda, Emilda (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The study aims to analyze the impact of incentives and punishments on the performance of Grab bike drivers Kota Palembang. The research method uses a quantitative approach by distributing a questionnaire to 97 respondents who are grab bike drivers in Palembang City. The analytical technique used is a double linear regression analysis processed using the help of the computer program Statistical Product and Service Solution (SPSS) version 25. Based on the test results of the partial hypothesis t on the incentive variable showed that a value of 7,969 > 1,986 with a significance value of 0,000 < 0,05 and the punishment variable indicated a values of 4,296 > 1 986 with the significance of 0.000 < 0,05 indicated that the incentives and punishments hypotheses had a positive and significant influence on driver performance. Based on the results of the determination coefficient test (R2), the known great impact of incentive and punishment on the performance of Grab bike drivers Kota Palembang is 69.9% and based on the calculation of the F test the hypothesis is accepted if Fcount > Ftabel or 95,034 > 3,09. Thus it can be concluded that there is a positive and significant influence on incentives and punishments on driver performance simultaneously or together.